A Potent Antibrowning Agent from Pine Needles of Cedrus deodara: 2R, 3R‐Dihydromyricetin. Issue 9 (27th August 2014) - Liang, Xue; Wu, Yan‐Ping; Qiu, Jing‐Hong; Zhong, Kai; Gao, Hong
Abstract This article focuses on finding the novel antibrowning agents from the pine needles of Cedrus deodara and studying its antibrowning effect. By bioassay guide of tyrosinase inhibitory activity, the main active compound was isolated and purified from 50% methanol extract of pine needles of C. deodara through macroporous resin Diaion HP‐20 column chromatography and high‐performance liquid chromatography. Based on mass and nuclear magnetic resonance data, the active compound was identified as 2R, 3R‐dihydromyricetin, which showed the potent monophenolase and diphenolase inhibitory activities. Moreover, 2R, 3R‐dihydromyricetin exhibited a strong ABTS radical scavenging activity with a dose‐dependent manner. The antibrowning efficacy of 2R, 3R‐dihydromyricetin was evaluated by monitoring the changes of L*, a*, and b* values and total color difference (△E) on fresh‐cut apple slices. It was found that 2R, 3R‐dihydromyricetin was effective in inhibiting the browning of apple slices treated with a concentration as low as 0.05% at 25 °C for 24 h. Its antibrowning effect was significantly better than ascorbic acid (0.5%) alone. Furthermore, 2R, 3R‐dihydromyricetin showed a good synergistic antibrowning effect with ascorbic acid. This is the first report that 2R, 3R‐dihydromyricetin from pine needles of C. deodara may be used as a potential antibrowning agent in protecting against food browning.